1996
DOI: 10.1128/mcb.16.4.1543
|View full text |Cite
|
Sign up to set email alerts
|

Protein Polymorphism Generated by Differential RNA Editing of a Plant Mitochondrial rps12 Gene

Abstract: The rps12 gene transcripts encoding mitochondrial ribosomal protein S12 are partially edited in petunia mitochondria. Different petunia lines were found vary in the extent of rps12 transcript editing. To test whether multiple forms of RPS12 proteins are produced in petunia mitochondria as a result of partial editing, we probed mitochondrial proteins with specific antibodies against edited and unedited forms of a 13-amino-acid RPS12 peptide spanning two amino acids affected by RNA editing. Both antibodies react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Thus, it would be expected that the mitochondrially encoded proteins that are synthesized in excess and not assembled into complexes would be degraded by specific protease activities, such as the one described by Sarria et al (1998). This does not seem to be happening to the same extent in the case of ATP1, COB, and NAD9 (i.e., their abundance does not decrease as much as the abundance of the nuclear-encoded subunits of the same complexes), but results from other experimental plant systems (Lu et al, 1996) and yeast (reviewed in Rep and Grivell, 1996) suggest that rapid degradation of nonfunctional or unassembled mitochondrially encoded proteins seems to be the norm in mitochondria.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, it would be expected that the mitochondrially encoded proteins that are synthesized in excess and not assembled into complexes would be degraded by specific protease activities, such as the one described by Sarria et al (1998). This does not seem to be happening to the same extent in the case of ATP1, COB, and NAD9 (i.e., their abundance does not decrease as much as the abundance of the nuclear-encoded subunits of the same complexes), but results from other experimental plant systems (Lu et al, 1996) and yeast (reviewed in Rep and Grivell, 1996) suggest that rapid degradation of nonfunctional or unassembled mitochondrially encoded proteins seems to be the norm in mitochondria.…”
Section: Discussionmentioning
confidence: 96%
“…In our study we could identify two of the eleven editing sites in P. patens mitochondria to be partially edited. A resulting protein heterogeneity from diVerentially edited RNAs was reported in one case (Lu et al 1996;Phreaner et al 1996) but not in others (Lu and Hanson 1994;Williams et al 1998). There is as yet no reasonable evidence for an additional level of modulating protein heterogeneity with physiological consequences through partially edited mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of examples of RNA processing in restored lines of various species that results in the production of a monocistronic transcript of the linked mitochondrial gene. In a few CMS systems that feature essential genes within the CMS-associated region, the expression of a closely linked gene, such as petunia rps12 and maize atp4 (Prioli et al, 1993;Lu et al, 1996), has been examined at the protein level and found not to be abnormal. Similar analyses of the expression of the genes shown in many of the CMSassociated regions in Figure 1 wait to be performed.…”
Section: Is the Expression Of Linked Genes Affected?mentioning
confidence: 99%